Laparoscopic repair of the uterine scar defect – successful treatment of secondary infertility: a case report and literature review - Bakavičiūtė, Greta; Špiliauskaitė, Sabina; Meškauskienė, Audronė; Ramašauskaitė, Diana (Acta medica Lituanica, 2017)
Background. The aim of this paper is to present a clinical case of laparoscopic repair of a uterine scar defect, to assess the effectiveness of treatment reviewing the latest literature sources, and to provide recommendations of uterine scar defect management. Materials and methods. We report the case of a 33-year-old woman with an insufficient uterine scar and one-year history of secondary infertility. Following this, she underwent corrective laparoscopic repair, successfully got pregnant two months later and carried pregnancy to full term. We discuss the prevalence of caesarean scar defects, their clinical symptoms, diagnostic methods, various treatment techniques, and their outcomes. Results and conclusion. Caesarean scar defects, insufficient uterine scars, isthmocele or scar dehiscence following a caesarean section involve myometrial discontinuity at the site of a scar previous caesarean section. These anatomical defects associated with prolonged menstrual bleeding, chronic pelvic pain, dysmenorrhea, dyspareunia and secondary infertility. Laparoscopic repair of the uterine scar defect is an effective method of treatment of secondary infertility. Patients with a previous history of caesarean section who present complaints of secondary infertility, need a detailed evaluation of the uterine scar before planning future pregnancies.